Biocontrol of sheep blowfly: is there a role for pathogen-based biopesticides?. Issue 1 (2nd January 2020) - Leathwick, Dave M.; Wright, David A.; Hurst, Mark R. H.
ABSTRACT: Blowflies cause a serious and debilitating disease of sheep in many countries. Reliance on the prophylactic use of chemicals for sheep protection is threatened by resistance and increasing awareness of the non-target and environmental consequences of their use. Further, consumer awareness of animal welfare issues is highlighting both the disease itself and some of the practices used to prevent it. Alternative approaches to fly control will likely be needed in future to maintain production and welfare levels. A range of fungal and bacterial pathogens are known to attack blowflies with some previously being investigated as potential biopesticides, however, to date none have been commercialised. Although much still remains to be discovered, the host–pathogen interaction appears complicated with the pathogen producing a range of compounds to facilitate invasion of the host and evasion of host defence mechanisms. While bacteria need to be ingested to infect a host, fungi appear to primarily invade through the cuticle. Fungal infection of adult flies can occur rapidly through the tarsi suggesting that only limited tactile contact is required. Many pathogens are intolerant of high temperatures such that their utility as prophylactic treatments, applied to sheep, may be limited. Also, while infected flies may not die rapidly, infection may result in behavioural changes and reduced fecundity, factors which need to be considered when evaluating the impact of pathogens. The use of pathogens in lure-and-kill strategies against adult flies or applied to pastures targeting pupal stages warrants further investigation.